The relationship between climate change and mental health: a systematic review of the association between eco-anxiety, psychological distress, and symptoms of major affective disorders - Suzanne M. Cosh; Rosie Ryan; Kaii Fallander; Kylie Robinson; Josephine Tognela; Phillip J. Tully; Amy D. Lykins (BMC Psychiatry, 2024)
Abstract Background and objectives The adverse impacts of climate change on mental health is a burgeoning area, although findings are inconsistent. The emerging concept of eco-anxiety represents distress in relation to climate change and may be related to mental health. The aim of this study was to explore the relationship between eco-anxiety with validated mental health outcomes, specifically psychological distress and symptoms of major affective disorders. Design Systematic review. Methods EBSCO, ProQuest, and Web of Science databases were searched to February 2024 for studies of adult samples quantifying eco-anxiety (exposure, i.e. fear, worry or anxiety in relation to climate change) and symptoms of psychological distress and major affective disorders (outcomes), as assessed by validated measures. Results Full text review of 83 studies was performed, and k = 35 studies were included in the review (N = 45 667, 61% female, M age 31.2 years). Consistently, eco-anxiety showed small to large positive correlations with mental health outcomes of psychological distress, depression symptoms, anxiety symptoms, and stress symptoms. However, results regarding post-traumatic stress disorder symptoms and pathological worry were mixed. Stronger associations were observed where eco-anxiety was operationalised as ‘anxiety’ rather than ‘worry’. Conclusions Findings underscore that eco-anxiety is related to psychological burden. Greater consideration of eco-anxiety in assessment and treatment is needed in clinical practice and further policy development is warranted at the intersection of climate and health to address the mental health challenges posed by climate change.